Detection of SYT–SSX fusion transcripts in both epithelial and spindle cell areas of biphasic synovial sarcoma using laser capture microdissection. Issue 2 (1st April 2000) - Kasai, T; Shimajiri, S; Hashimoto, H
Abstract : To investigate the distribution of tumour cells expressing the SYT–SSX fusion gene in biphasic synovial sarcoma, modified reverse transcription polymerase chain reaction (RT–PCR) analysis was performed using microdissected specimens from haematoxylin and eosin stained sections of archival paraffin wax embedded tissues. This modified RT–PCR included a stage with degenerate oligonucleotide primed (DOP) PCR, which randomly amplified cDNA after reverse transcription. SYT–SSX fusion transcripts were detected in both epithelial and spindle cell areas of all three biphasic synovial sarcomas examined. Subsequent sequence analysis confirmed that the detected messages were derived from the SYT–SSX1 fusion gene in two cases and from SYT–SSX2 in one. These results indicate that SYT–SSX fusion transcripts are found in both epithelial and spindle cell areas of biphasic synovial sarcoma, and RT–DOP–PCR–PCR analysis is a useful method for detection of extremely small amounts of mRNA in microdissected samples from archival formalin fixed, paraffin wax embedded tumour tissues.